International legal personality in public and private law: problems of theory and practice - Pahlevanzade, Alborz; Panova, Liydmyla; Gramatskyy, Ernest; Panov, Alen; Sarybaieva, Ganna (My University, 2021)
At the present stage of the development of international relations, an important aspect is the specification of the rights and obligations of the subjects of international law, which are elements of international legal personality, which is subject to multifaceted study. The research of its problematic elements is fundamental to improving the rules of international law in general and domestic law in particular. The work aims to study and identify problems of theory and practice of international legal personality in public law. The object of research is international legal personality in public law. The subject of the research is problematic aspects of the theory and practice of international legal personality in public law. The following methods were used in the study: observation, historical method, method of analysis, comparison, generalization, the system method, method of analysis of normative documents. As a result of the research, the institute of international legal personality, in general, was analyzed, its peculiarities and problematic aspects were determined.
Sarybaieva G. International legal personality in public and private law: problems of theory and practice / A. Pahlevanzade, G. Sarybaieva, A. Panov, E. Gramatskyy, L. Panova // Amazonia Investiga. – 2021. – Vol.10, Issue 47. – P. 180-189.
Keywords: international legal personality; public law; public international law; subjects of international law